KESEMARAKAN PELAKSANAAN HARI SUCI SARASWATI DI BERBAGAI LEMBAGA PENDIDIKAN - I Ketut Wartayasa (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2023)
The celebration of Saraswati Day is very lively in formal educational institutions. At schools, colleges, all children and students welcome cheerfully and happily, of course, the atmosphere displayed is also different from everyday life. It's not only at school that Saraswati Day is celebrated in the family environment. In the past, Saraswati was only performed in Gria-gria, in a puri or in a certain place, so in subsequent developments it has become a holiday that is welcomed by all Hindus. The celebration of Saraswati shows that Hindus crave and glorify knowledge because knowledge exalts human life. In addition, knowledge has been proven to make human life easier. In Hindu literature there is praise for the greatness of this knowledge. In Bali, Dewi Saraswati, who is also called Vagisvari and Dhatridewi, whose symbol is better known is in the form of script (in this case the Balinese script). Besides being a symbol of sound, the Balinese script also contains sacred scripts that contain magical values, such as the modre script, loka natha, which is used in Aji Kadhyatmikan and the like. Keywords: Saraswati Day, Education